Therapeutic Targeting of Cancer: Epigenetic Homeostasis - Yu, Xiaoyuan; Li, Menglu; Guo, Chunyan; Wu, Yuesheng; Zhao, Li; Shi, Qinying; Song, Jianbo; Song, Bin (Frontiers in Oncology, 2021)
A large number of studies have revealed that epigenetics plays an important role in cancer development. However, the currently-developed epigenetic drugs cannot achieve a stable curative effect. Thus, it may be necessary to redefine the role of epigenetics in cancer development. It has been shown that embryonic development and tumor development share significant similarities in terms of biological behavior and molecular expression patterns, and epigenetics may be the link between them. Cell differentiation is likely a manifestation of epigenetic homeostasis at the cellular level. In this article, we introduced the importance of epigenetic homeostasis in cancer development and analyzed the shortcomings of current epigenetic treatment regimens. Understanding the dynamic process of epigenetic homeostasis in organ development can help us characterize cancer according to its differentiation stages, and explore new targets for cancer treatment based on transdifferentiation, improving the clinical prognosis of patients with cancer.